1983
DOI: 10.1021/i300010a010
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic amination of aliphatic alcohols in the gas and liquid phases: kinetics and reaction pathway

Abstract: The kinetics of the copper-catalyzed amination of long-chain aliphatic alcohols (octanol and decanol) by monomethylamine and dimethylamine have been investigated in both the gas and liquid phases at temperatures between 440 and 540 K. The individual reactions leading to the production of stable intermediates and products are identified. The rate of dehydrogenation of the alcohol determines the overall rate of alcohol conversion to all products. The rate is first order in alcohol in both the gas and liquid phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 4 publications
2
50
1
Order By: Relevance
“…In our case, the ethanolamine inhibitor molecule contains both the amino and hydroxyl functional groups, and can undergo intermolecular dehydroamination reactions. Kinetic studies [49,50] have shown that the dehydroamination reaction dominates on copper catalyst surfaces at the temperatures of our experiments, and displaces other feasible catalytic reactions such as amine disproportionation. As a consequence, one contribution to the inhibiting action of ethanolamine is based on competitive adsorption: bromobenzene is displaced from the catalytically active sites, which are blocked by the ethanolamine involved in dehydroamination reactions.…”
Section: Inhibition Of Dehalogenation By Ethanolamine Additionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our case, the ethanolamine inhibitor molecule contains both the amino and hydroxyl functional groups, and can undergo intermolecular dehydroamination reactions. Kinetic studies [49,50] have shown that the dehydroamination reaction dominates on copper catalyst surfaces at the temperatures of our experiments, and displaces other feasible catalytic reactions such as amine disproportionation. As a consequence, one contribution to the inhibiting action of ethanolamine is based on competitive adsorption: bromobenzene is displaced from the catalytically active sites, which are blocked by the ethanolamine involved in dehydroamination reactions.…”
Section: Inhibition Of Dehalogenation By Ethanolamine Additionmentioning
confidence: 63%
“…Both types of molecules have recently been identified as intermediates in the copper-catalyzed condensation reaction of aliphatic alcohols and amines on copper catalysts [49]. This class of reactions involves copper-catalyzed dehydrogenation and hydrogenation steps, and has been termed dehydroamination [50].…”
Section: Inhibition Of Dehalogenation By Ethanolamine Additionmentioning
confidence: 99%
“…Depending on the reactants (alcohol and amine), various amines can be produced by catalytic amination. Alcohols used so far include simple aliphatic alcohols [2][3][4]18], alcohols which contain a substituent in the aliphatic chain such as alkoxy-alcohols [19], phenoxyalkyl alcohols [20], and phenyl-alkyl alcohols [21].…”
Section: Amination Of Alcoholsmentioning
confidence: 99%
“…Based on identified products, on the response of activity and selectivity to changes in the reaction parameters, and on experiments with isotope-labeled alcohols [18], the amination of aliphatic alcohols was suggested to occur via the intermediates shown in Scheme 1. For the sake of simplicity, the interaction of reactants, intermediates and products with the metal surface (e.g., dissociative adsorption) is not specified.…”
Section: Amination Of Alcoholsmentioning
confidence: 99%
“…From the economic point of view, the production of industrially important amino compounds usually starts from more available alcohols, the hydroxyl group of which is first converted to the more reactive carbonyl group on the surface of the metallic catalyst. Nucleophilic addition of amination agents to the carbonyl group then provides imines (R-N=C-R) or enamines (R-C=C-N-R) that are subsequently easily hydrogenated to particular primary, secondary, or tertiary amines [1][2][3][4][5] . Special group of amines is amino alcohols containing both hydroxyl and amino group in their molecule.…”
Section: Introductionmentioning
confidence: 99%